PENGEMBANGAN E-BOOKLET JAMUR BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN HASIL BELAJAR PADA PEMBELAJARAN BIOLOGI - Sri Utami Ningsih; Indri Astuti; Aloysius Mering (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to develop the design, profile of mushroom e-bookletlearning media based on local wisdom and improve learning outcomes,including critical thinking, creative thinking and students' mastery ofconcepts (cognitive) in class X, majoring in Science at SMAN 3 Sintang. Thedevelopment method used refers to the design model by Walter Dick, LouCarey, and James Carey which includes pre-development, development, andpost-development. The results of data analysis show (1) students aremotivated to learn (2) positive responses from students with an averagescore Average Content Validity Ratio (CVR) = 0.99 - 1 and Content ValidityIndex (CVI) = 0.99-1, (2) there is an increase in learning outcomes in termsof critical thinking, creative thinking and cognitive students with an averagevalue of average before using mushroom e-booklet media (pretest) = 57.13to 82.53 after using mushroom e-booklet media (posttest). Thus it isconcluded that the e-booklet media is effective as a learning medium withthe level of media effectiveness calculated using Cohen's criteria is worth3.20 or very influential (very strong).Keywords: E-booklet, Effectiveness, Learning media, , Local wisdom, ,Increasing learning outcomes